THE GENDER FEATURES OF THE RENIN-ANGIOTENSIN-ALDOSTERONE SYSTEM IN HYPERTENSIVE PATIENTS - V. I. Podzolkov; A. E. Bragina; Ju. N. Rodionova; E. K. Panferova (Столичная издательская компания, 2016)
Aim. To study the correlation of the renin-angiotensin-aldosterone system (RAAS) activity with the female sex hormone levels and markers of target organ damage in patients with arterial hypertension (HT).Material and methods. Patients with HT (20 men and 39 postmenopausal women) were involved into the study. The dynamic renal angioscintigraphy and echocardiography were performed, plasma rennin activity (PRA), levels of aldosterone, estradiole and 17-hydroxiprogesterone were determined by radioimmunoassay.Results. Higher aldosterone level was found in women in comparison with men (212,5±123,9 pg/ml and 148,9±82,5 pg/m, respectively, р=0,03). Negative relations between aldosterone and estradiol levels (r=-0,3; p=0,04), and between aldosterone and 17-hydroxyprogesterone levels (r=-0,318; p=0,04), and positive relations between aldosterone concentration and PRA (r=0,555; p=0,04) was found in women. Besides, correlation between levels of female sex hormones, aldosterone and renal blood flow indicators, glomerular filtration rate, left ventricular mass index (LVMI) were found in women. These correlations were not found in men.Conclusion. The gender differences of RAAS activity were revealed with higher aldosterone level in postmenopausal hypertensive women in comparison with men. Relationships between PRA, levels of aldosterone and female sex hormones and renal blood flow indices, LVMI were also found in women.